واقع دار المسنين دراسة ميدانية في مدينة السليمانية - فرج, أ.د.نجاة محمد; صابر, أ.د.نيان نامق; عزيز, د.شاگوڵ كمال; اسماعيل, د.بختيار خالد (Sulaimani Journal for Humanities, 2023)
The current research aims to identify the reality of elderly home in the city of Sulaimani through the following objectives: 1- Identifying the psychological, social and health conditions of the ages. 2- Identifying the most important problems of the elderly home. 3- Identifying the difficulties faced by the elderly home. This research is a qualitative (exploratory and descriptive) method, by using the case study method and thematic analyses. The research community included all ages and cadres in the Elderly Shelter located in the Social Care Complex of the Directorate of Labor and Social Affairs in the city of Sulaymaniyah. The method of (comprehensive enumeration) of the inmates of the house was relied upon in order to achieve the objectives of the research, as their number reached (49) elderly, but due to the injury of (24) cases with complete disability, this prevented the possibility of conducting interviews with those cases, so the research sample became (25) cases They were interviewed to study their realistic psychological and social conditions in the home. As for the sample of the functional cadres in the house, they numbered (6) cadres, in order to achieve the objectives of the second and third research, and it is a sample (Non probability intentional). The interview, observation, records and documents were used as research tools. The research has reached a set of results, including: Among the reasons for resorting to the home are the lack of a place to live in, the existence and cases of divorce, the loss of a partner, and celibacy. Among the most important psychological and social problems that the elderly suffer from are many psychological disorders, in addition to their lack of a family atmosphere, and the lack of a permanent psychologist who they desperately need. As for the problems that the home suffers from, the building is not suitable for the nature of the age group, and the material needs are not met by the government. As for the difficulties facing the management of the home, it is represented in the interference of the higher authorities in the management of the home, as well as the sending of cases that do not conform to the instructions of the home by the court panel.
Keywords: Reality; elderly home; Sulaimani